Why men can only do one thing at a time And women never stop talking - Pease, Allan; Pease, Barbara (London Orion, 2003)
Fabulous combined giftbook edition of the two mini books WHY MEN DON'T LISTEN AND CAN ONLY DO ONE THING AT A TIME and WHY WOMEN CAN'T READ MAPS AND WON'T STOP TALKING
Keywords: Men -- Psychology. Women -- Psychology. Men -- Sexual behavior